A Survey on the Prevalence of Depression in Blood Donors with Hepatitis C in Shiraz - Kasraian, Leila (Hepat Mon, 2016)
BACKGROUND: Depression is the most common psychiatric disorder associated with hepatitis C. OBJECTIVES: This study aimed to survey the prevalence rate of depression in patients with Hepatitis C Virus (HCV) before they were aware of their HCV test result. METHODS: This cross-sectional study was conducted on all blood donors with confirmed positive HCV test results who donated blood between March 21, 2012 to March 21, 2013 at Fars blood transfusion center in Iran as case group and age- and sex-matched blood donors with negative screening test results as control group. A semi-structured interview based on DSM IV-TR depressive disorder criteria and Beck depression inventory (BDI) was conducted. BDI contained 21 items, each scored from 0 to 3 and total score of 0 to 63 for the whole scale computed by summing up all the items. A cut-off score of ≥ 19 indicated clinically significant depressive symptoms. The prevalence rate and risk factors of depression were determined. RESULTS: The most frequent risk factors for HCV infection were intravenous drug abuse (59.3%), unsafe sexual contact (30.5%), and history of being imprisoned (25.4%). The prevalence rate of depression in the HCV group was 55.9 % (95% CI: 42.99% - 68.87%) that was significantly higher than the corresponding rate of the control group as 17.7 % ( 95% CI: 8.49% - 28.79%) (P < 0.001). The severity of depression was also more in the HCV group (P < 0.001). Besides, the prevalence rate of depression was higher among HCV patients with lower education level, previous history of drug abuse, unsafe sexual contact, and previous history of psychiatric diseases. The prevalence rate of depression was higher in the case group even after adjusting for other variables. CONCLUSIONS: Our study underlined the remarkable prevalence of depression among HCV patients. Therefore, designing depression screening tests is suggested to help such patients before starting the treatment.